Achievability of Municipal Solid Waste Compost for Tea Cultivation with Special Reference to Cadmium. Issue 6 (30th March 2018) - Karak, Tanmoy; Abollino, Ornella; Paul, Ranjit K.; Dutta, Amrit K.; Giacomino, Agnese; Khare, Puja; Boruah, Romesh K.
Abstract : Municipal solid waste compost (MSWC) is quite often used for soil amendment in agricultural crops and yet little is known about its effect on tea ( Camellia sinensis L.) cultivation. This study investigates the effect of MSWC application on cadmium (Cd) concentrations in soil, tea plants, and infusions. Different doses of MSWC are added to soil with two Tocklai vegetative (TV) tea clones (TV1 and TV23) for 2 years in pot experiments. Several fractions of Cd in amended soils, biomass yield, and Cd content in different parts of tea plants and in tea infusions are measured. Several indexes related to risk assessment are also calculated. The geo‐accumulation index values of Cd in soil amended with MSWC ranges from −1.74 to 3.12, indicating class 0 (practically uncontaminated) to class 4 (heavily contaminated) contamination level. Average daily intakes (ADI) of Cd through tea infusion produced from tea plant amended with MSWC are 8.9 × 10 −6 and 9.2 × 10 −6  mg kg −1 per body weight and day for men and women, respectively. These values are much lower than those given in the Joint FAO/WHO Provisional Tolerable Monthly Intake Guideline for Cd. The non‐carcinogenic risk values (also called hazard quotient) for Cd, estimated from the ADI values, are found to be 1.78 × 10 −2 and 1.94 × 10 −2  mg kg −1 per day for men and women, respectively, suggesting no health hazard. The results suggested the possibility of management of MSW through composting and the feasibility of compost application for tea cultivation. Abstract : Municipal solid waste compost (MSWC) application in tea cultivation is usually criticized due to the presence of heavy metals like Cd. The present study reports Cd accumulation in tea plants ( Camellia sinensis L.) grown in MSWC‐amended soil and its transfer to infusion.